Pengaruh kualitas pelayanan terhadap kepuasan pengunjung di The Legend Star Park Jawa Timur Park 3 Batu - Firdausi, Hilda Sabila; Alvianna, Stella; Puspawigati, Ani; 'Ulya, Ayu Fitriatul (Jurnal Pariwisata Tourista, 2024)
Â This study aims to determine the effect of service quality on visitor satisfaction at The Legend Star Park, Jawa Timur Park 3 Batu. The Legend Star Park is one of the most popular tourist destinations in Jawa Timur Park 3. On weekends or national holidays it is always full of visitors. However, there is still a lack of tourist interest in visiting The Legend Star Park among other main tourist attractions in Jawa Timur Park 3. The method used in this study is a quantitative method. The research sample will be taken as many as 100 respondents from visitors who have visited The Legend Star Park. The sampling technique uses probability sampling by distributing questionnaires as a data collection instrument. To determine the answer scores on the questionnaire using a Likert scale which will be tested using statistical methods, namely validity testing, reliability testing, classical assumption testing and hypothesis testing. The results showed that there was a significant influence of service quality on visitor satisfaction at The Legend Star Park, Jawa Timur Park 3 Batu. It can be concluded that the existence of good service quality can have a positive effect on the level of visitor satisfaction.Â